2011
DOI: 10.1038/onc.2011.46
|View full text |Cite
|
Sign up to set email alerts
|

Sds22/PP1 links epithelial integrity and tumor suppression via regulation of myosin II and JNK signaling

Abstract: Loss of epithelial integrity often correlates with the progression of malignant tumors. Sds22, a regulatory subunit of Protein Phosphatase 1 (PP1), has recently been linked to regulation of epithelial polarity in Drosophila. However, its role in tumorigenesis remains obscure. Here, using Drosophila imaginal tissue as an in vivo model system, we show that sds22 is a new potential tumor suppressor gene in Drosophila. Without sds22, cells lose epithelial architecture, and become invasive and tumorigenic when comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 64 publications
2
41
0
Order By: Relevance
“…Myosin II activity has also been linked to JNK activation in a study of the Drosophila non-muscle myosin phosphatase PP1β (Flapwing), which negatively regulates JNK activity through the inhibition of Myosin II activity in the developing wing (Kirchner et al, 2007). Furthermore, a recent study has shown that depletion of the Sds22/PP1 phosphatase can cooperate with Ras ACT , via upregulation of Myosin II activity and JNK activation (Jiang et al, 2011). However, in all of these studies, cell morphology changes occur and might induce recruitment of haemocytes and the activation of JNK via the extrinsic TNF (Egr) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Myosin II activity has also been linked to JNK activation in a study of the Drosophila non-muscle myosin phosphatase PP1β (Flapwing), which negatively regulates JNK activity through the inhibition of Myosin II activity in the developing wing (Kirchner et al, 2007). Furthermore, a recent study has shown that depletion of the Sds22/PP1 phosphatase can cooperate with Ras ACT , via upregulation of Myosin II activity and JNK activation (Jiang et al, 2011). However, in all of these studies, cell morphology changes occur and might induce recruitment of haemocytes and the activation of JNK via the extrinsic TNF (Egr) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Scribble has also been shown to form a complex with SHOC2/SUR-8 (PP1 phosphatase regulator) and MRAS (RRas subgroup of Ras proteins), and Scribble blocks SHOC2-mediated dephosphorylation of RAF (a protein kinase downstream of Ras) at the conserved inhibitory site (S259), thereby inhibiting RAF activation (Young et al 2013). This mechanism appears to be conserved in Drosophila, where the deregulation of PP1 activity contributes to the scrib mutant phenotype, but in this case it appears to function via regulation of the JNK stress response signaling (Jiang et al 2011). As described above (see Sect.…”
Section: Rtk-ras-mapk/jnk/p38mentioning
confidence: 90%
“…4.4.9), scrib loss of function leads to the activation of the JNK pathway (Brumby and Richardson 2003;Uhlirova et al 2005), which together with Ras activation (Ras V12 ) leads to invasive tumor formation (Leong et al 2009;Igaki et al 2006;Uhlirova and Bohmann 2006). Overexpression of a PP1 regulator, Sds22, blocks scrib-Ras V12 tumorigenesis, by inhibiting Myosin II and JNK activity and preventing cell invasion/metastasis (Jiang et al 2011).…”
Section: Rtk-ras-mapk/jnk/p38mentioning
confidence: 98%
“…JNK can inhibit cell differentiation and tissue growth and promote cell invasion. Myosin II is required for cell contractility, cytoskeleton reorganization and cytokinesis [167]. The above molecules interplay together to accelerate cooperative tumorigenesis.…”
Section: Myosin-mediated Factors Pathways and Models During Tumorigementioning
confidence: 99%
“…The expression level of PP1 is invariably decreased in cancer cells and the PP1 inhibitor, okadaic acid, can promote tumor invasion and metastasis development [170]. The reasonable interpretation is that PP1 can efficiently inhibit the phosphorylation of myosin II and JNK, thus restricting tumor progression [167]. Furthermore, JNK partly mediates the expression of MMP1 (Matrix metalloprotease 1), which can facilitate cell motility [171] and the degradation of the basement membrane [172], which are both related to tumor malignancy potential [173].…”
Section: Myosin-mediated Factors Pathways and Models During Tumorigementioning
confidence: 99%